The Effects of Mild Intermittent Hypoxia Exposure on the Abdominal Subcutaneous Adipose Tissue Proteome in Overweight and Obese Men: A First-in-Human Randomized, Single-Blind, and Cross-Over Study - Van Meijel, Rens L. J.; Wang, Ping; Bouwman, Freek; Blaak, Ellen E.; Mariman, Edwin C. M.; Goossens, Gijs H. (Frontiers in Physiology, 2022)
Adipose tissue (AT) oxygen tension (pO2) has been implicated in AT dysfunction and metabolic perturbations in both rodents and humans. Compelling evidence suggests that hypoxia exposure alters metabolism, at least partly through effects on AT. However, it remains to be elucidated whether mild intermittent hypoxia (MIH) exposure impacts the AT proteome. We performed a randomized, single-blind, cross-over study to investigate the effects of seven consecutive days of MIH (FiO2 15%, 3x2h/d) compared to normoxia (FiO2 21%) exposure on the AT proteome in overweight/obese men. In vivo AT insulin sensitivity was determined by the gold standard hyperinsulinemic-euglycemic clamp, and abdominal subcutaneous AT biopsies were collected under normoxic fasting conditions following both exposure regimens (day 8). AT proteins were isolated and quantified using liquid chromatography-mass spectrometry. After correction for blood contamination, 1022 AT protein IDs were identified, of which 123 were differentially expressed following MIH (p < 0.05). We demonstrate for the first time that MIH exposure, which markedly reduces in vivo AT oxygen tension, impacts the human AT proteome. Although we cannot exclude that a single differentially expressed protein might be a false positive finding, several functional pathways were altered by MIH exposure, also after adjustment for multiple testing. Specifically, differentially expressed proteins were involved in redox systems, cell-adhesion, actin cytoskeleton organization, extracellular matrix composition and energy metabolism. The MIH-induced change in AT TMOD3 expression was strongly related to altered in vivo AT insulin sensitivity, thus linking MIH-induced effects on the AT proteome to metabolic changes in overweight/obese humans.